Global, regional, and national prevalence and trends of gynecological diseases among women of childbearing age from 1990 to 2021: An analysis of the global burden of disease study 2021 - Xiaofeng He; Jiao Su; Kunbo Wang; Yuanhao Liang; Long Wang (PLoS ONE, 2025)
Purpose The global prevalence and trends of gynecological diseases (GDs) among women of childbearing age (WCBA) remain unclear and may be underestimated. This study aims to evaluate the prevalence of GDs at global, regional, and national levels and assess changes from 1990 to 2021. Methods Data on the annual prevalence of major GDs, including uterine fibroids, polycystic ovarian syndrome (PCOS), female infertility, endometriosis, genital prolapse, premenstrual syndrome (PMS), and other GDs, were obtained from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021. The study analyzed women aged 15–49 years across 204 countries and territories from 1990 to 2021. Estimated annual percentage changes (EAPC) in the age-standardized prevalence rate (ASPR) were calculated to quantify temporal trends, by age and socio-demographic index (SDI). Results In 2021, the global prevalence of GDs among WCBA was estimated at 1.21 billion cases, corresponding to a ASPR of 62,091.73 cases per 100,000 population (95% UI: 62,088.24 to 62,095.23). While the ASPR for GDs remained stable from 1990 to 2021 (EAPC = 0% [95% CI: –0.03 to 0.02]), the number of prevalent cases doubled over the same period. In 2021, the most prevalent GD globally was PMS, followed by uterine fibroids, PCOS, and female infertility. Conditions such as uterine fibroids, PCOS, and female infertility showed a significant upward trend in ASPR over time. Additionally, the ASPR of most GDs generally decreased with rising SDI, except for PCOS, which exhibited an increasing trend with higher SDI. The prevalence of GDs also increased with age, peaking in the 40–44 years age group. However, a shift in the burden of GDs toward younger women was observed, with significant increases in prevalence rates for uterine fibroids, PCOS, female infertility, and PMS in women aged 20–29 years. Conclusions GDs among WCBA remain a global concern, underscoring the urgent need for targeted interventions, especially for younger populations and in regions with limited healthcare infrastructure. Prioritizing early intervention, addressing environmental risk factors, and removing barriers to healthcare access will mitigate the long-term impact of these conditions on women’s health and overall well-being.